Share a Smoke Club (Ithaca, N.Y.) records - Share a Smoke Club (Ithaca, N.Y.)
Correspondence, bylaws, minutes, reports, clippings, and other records. Correspondents include John M. Gauntlett.
War relief effort organized in 1939 by Harold H. Schaff to provide American cigarettes to British troops during World War II.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gauntlett, John M. -- Correspondence; Schaff, Harold H; Cigarettes; World War, 1939-1945 -- War work -- Great Britain; World War, 1939-1945 -- War work -- United States